Application Exploration of Multifunctional Hydrogels in Local Drug Delivery and Anti Inflammatory Microenvironment Construction - Zhou, Yang (International Journal of Public Health and Medical Research, 2026)
This paper examines the use of multi-functional hydrogels in local drug delivery and designs strategic anti-inflammatory microenvironments. Hydrogels are three-dimensional cross-linked polymeric networks with tunable properties that can serve as good biomaterials for spatiotemporal control of therapeutic agent release. At present, in terms of the main Design ideas of these biomaterials, emphasis is placed on stimuli-responsive architectures and injectable forms to achieve localised drug release at diseased tissues. In addition, this paper explores the way to integrate immunomodulatory drugs and functional nanomaterials more proactively into hydrogel carriers for treating local inflammation. Through organisation of macrophage polarisation, active remodelling of the pathological cellular niche can be achieved by the biomaterials, and they are thus transformed from passive delivery systems into dynamic therapeutic platforms. Synthesize relevant research papers to assess the effect of the above systems on chronic wound healing and tissue regeneration in solid tumour therapy. In addition, this paper will address the existing structural deficiencies and regulatory hurdles, as well as the future engineering optimisation directions required for the clinical translation of advanced hydrogel delivery systems. Standardisation of the manufacturing process and validation of long-term biological safety are still required for wider clinical application.